ECO-CONNECT ASEAN 2025 COMMUNITY SERVICE: A STUDY ON ECOTOURISM, GOVERNANCE, AND CROSS-NATIONAL COMMUNITY DIPLOMACY - Lestari, Linayati; Harahap, Dahrul Aman; Ramon Zamora; M. Sarif; Ali Amran; Wardi Marsis (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
The cross-border community service program under the theme Eco-Connect ASEAN 2025 was implemented on Tanjung Surat Island, Malaysia, with the support of the Johor Customs Office. This program was initiated in response to strategic issues related to the sustainable management of local resources, as well as an effort to strengthen people-to-people diplomacy among ASEAN countries. The primary objective of the program is to utilize Jong (traditional boats that serve as cultural identity and tourist attraction) and Kelulut honey (stingless bees with high economic and ecological value) as means for ecotourism development and local community empowerment. The methods employed included field observation, socialization and education, focused group discussions, and product branding workshops, with a participatory approach to ensure active community involvement. From a public administration perspective, the program emphasizes the strengthening of community-based ecotourism governance, the formation of cross-border networks, and support for achieving the ASEAN 2025 sustainable development agenda.The outcomes of the program include increased community awareness of the importance of ecotourism management, the establishment of discussion groups on Kelulut honey management, the creation of cross-border cooperation networks as part of the Eco-Connect ASEAN initiative, and enhanced community skills in optimizing local potential to support a sustainable economy.